PENGEMBALIAN STATUS HUKUM TANAH ULAYAT ATAS HAK GUNA USAHA - Jasmir, Jasmir (Soumatera Law Review, 2018)
Land tenure by the state does not mean possessed, but as the name of the land, grants only the right of access to land which can be given to the land, its designation, use and maintenance and its arrangement to the law and the relations it can do to those lands. Article 3 of the BAL is indeed available the term "customary rights and similar rights". This paper is a normative juridical study, which will discuss the status of ulayat right to the right of business in Indonesia. In 2012, the Constitutional Court granted most of the material of Law No. 41 of 1999 on Forests petitioned for the Alliance of Indigenous Peoples of the Archipelago (AMAN) and two indigenous communities namely Kanegerian Kuntu and Kasepuhan Cisitu. After the issuance of Regulation of the Minister of Agrarian Affairs No. 5 of 1999, the status of land of Hak Guna Usaha derived from customary community land from a limited period of time or Hak Guna Usaha which abolishes based on applicable provisions, which then the land is re-paid into the community ulayat right customary law.